Addressing the Issue of Stunting in Toddlers through the Provision of Supplementary Food in the Form of Moringa Pudding in the Village of Kupangan - Meylia, Nadira Zalfa; Yazidah, Syera Izatul; Nida, Aulia Qotrun; Wardiansyah, Anisa; Putri, Elza Rahma; Nasrulloh, Nasrulloh; Arifin, Fajar Nur; Fauzia, Zahra; Rahmadani, Anggita Uniek; Rochmah, Alfiatur Nur; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
The issue of stunting in Kupangan Village, Sukoharjo District, Wonosobo Regency prompted the Community Service Program group from Muhammadiyah University of Purwokerto to introduce moringa leaf pudding as an alternative supplementary food for toddlers. The program includes nutrition education and practical training in pudding making for mothers, health post volunteers, and members of the Women’s Empowerment Group. Moringa leaves were chosen due to their rich nutritional content, including protein, vitamins, minerals, and antioxidants, which play a crucial role in children’s growth and development. The training process was conducted using simple methods with easily accessible ingredients, enabling the pudding to be produced in a practical and economical manner. Based on the evaluation results, this innovation received a positive response and was well-liked by children, making it a promising solution for preventing stunting in the region.